2021
DOI: 10.1111/hdi.12960
|View full text |Cite
|
Sign up to set email alerts
|

Determination of problems experienced during the COVID‐19 pandemic by individuals receiving hemodialysis treatment

Abstract: Background Patients receiving hemodialysis treatment are among the risk groups during the COVID‐19 pandemic. They must cope with many factors simultaneously like anxiety about being ill, social isolation, inadequate information about protective precautions, and the need to attend regular treatment. Objectives This study was performed with the aim of determining problems experienced by individuals receiving hemodialysis treatment during the pandemic. Design This was a descriptive and cross‐sectional type study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In this investigation, depression and perceived stress were prominent contributors to poor sleep quality among dialysis patients. In the COVID‐19 outbreak, haemodialysis patients travel between home and healthcare facilities (Yu et al, 2021 ), are at constant risk of contracting the virus, and are under tremendous pressure on their health and their families (Bulbul et al, 2022 ; Lv et al, 2022 ). In addition, loneliness, fear of death, and financial concerns are stressors that lead to anxiety and depression during the COVID‐19 pandemic, and the poor sleep quality caused by such stress is expected (Duru, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, depression and perceived stress were prominent contributors to poor sleep quality among dialysis patients. In the COVID‐19 outbreak, haemodialysis patients travel between home and healthcare facilities (Yu et al, 2021 ), are at constant risk of contracting the virus, and are under tremendous pressure on their health and their families (Bulbul et al, 2022 ; Lv et al, 2022 ). In addition, loneliness, fear of death, and financial concerns are stressors that lead to anxiety and depression during the COVID‐19 pandemic, and the poor sleep quality caused by such stress is expected (Duru, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the early COVID-19 pandemic, many countries implemented nationwide lockdowns in line with containment policies. However, the patients with MHD need to commute between home and a hospital regularly by public transportation, and stay with doctors, nurses or other patients in a shared space for at least 8–12 h per week due to the specificity of the dialysis treatment, which makes the patients cannot help but to face a complex medical and social environment, resulting in an increased concern about the transmission of COVID-19 by medical staff, infection of themselves or their family members and the surrounding environment, and serious reduction in socialization ( 10 ). As susceptible populations of anxiety, under the combined action of above factors, fear and apprehension induced by COVID-19 may aggravate the psychological disorders of the patients with MHD ( 10 , 30 33 ), resulting in the aggravation of anxiety symptoms, manifested as shortness of breath, accelerated heart rate, pain, nervousness, and insomnia ( 10 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three studies using SAS as diagnostic tools have shown that 34.89%-44.90% of the patients with MHD have elevated anxiety symptoms ( 9 , 38 , 39 ). Several studies investigated that monthly income, education, work situation, medical insurance, dialysis duration, epidemic propaganda, and physical condition are closely associated with the elevated anxiety syndrome ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation